Wearable Respiration Sensor for Continuous Healthcare Monitoring Using a Micro‐Thermoelectric Generator with Rapid Response Time and Chip‐Level Design. Issue 8 (9th February 2022) - Yu, Yuedong; Zhu, Wei; Zhou, Jie; Guo, Zhanpeng; Liu, Yutong; Deng, Yuan
Abstract: Thermoelectric generators (TEG) serve as excellent passive wearable sensors for monitoring human body heat. However, a micro‐TEG (μTEG) with chip‐level size, rapid response, and high and stable responsivity is desired for real‐time and full‐time respiration monitoring to predict and diagnose breath‐related diseases. In this study, a thin‐film compact μ TEG is elaborately designed by combining an ultrathin vertical structure for rapid heat conduction and a horizontal high‐integration density for transient response and a high filling rate. The device integrated with 28‐pair micro thermoelectric (TE) legs is fabricated on an aluminum nitride (AlN) substrate, which is patterned using ultrafast laser direct writing with embedded bottom contacts and TE legs. This unique design of the proposed μ TEG provides a rapid response of 8 ms and chip‐level size of 1.9 mm × 2.7 mm × 400 μ m for easy wearability. Additionally, application scenarios of real‐time respiration monitoring are demonstrated by mounting the μTEG under the nostril and near the mouth. The recorded airflow signals are displayed precisely with distinct features separating the nose and mouth breathing. Thus, the study presents a subtle and wearable respiration sensor for real‐time and full‐time human physiological signal acquisition. Abstract : A wearable respiration sensor based on micro‐thermoelectric generators with ultrathin vertical structure and high‐integration density is designed and fabricated. It offers a fast response speed of up to 8 ms for heat flow and a chip‐level size for wearability (1.9 mm × 2.7 mm × 400 µm). Therefore, the proposed design is promising for full‐time human physiological monitoring.